MODELING OF THE INFLUENCE OF THE THERMOMECHANICAL MODIFICATION PARAMETERS ON THE STRUCTURAL CHANGES IN POLYESTER FIBERS: MODELING OF THE INFLUENCE OF THE THERMOMECHANICAL MODIFICATION PARAMETERS ON THE STRUCTURAL CHANGES IN POLYESTER FIBERS - Velev, Valentin; Grozev, Valentin; Popov, Anton; Androsch, Rene; Dimov, Todor; Veleva, Lyubomira; Radusch, Hans-Joachim (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the present work is proposed an attempt for modeling of the complex influence of the heat mechanical treatment parameters on the structure developments in as-spun polyester fibers. Freshly molded poly(ethylene terephthalate) (PET) filaments with different preliminary orientation were subjected to simultaneously thermal and mechanical treatments. PET yarns were sequentially undergoing to uniaxially strain-stress with values of 40 MPa, 80 MPa, and 120 MPa at three different temperatures in a narrow temperature range from 850C to 950C. Differential scanning calorimetry (DSC) has been used to study the structural rearrangements in the heat-mechanically processed PET fibers. Response equations have been obtained showing the relationship between the parameters of the thermal deformation experiment and the desired degree of crystallinity of the studied PET fibers.